Influence of Organic Molecules on the Luminescent Properties of Composites Based on CdS Quantum Dots - Smyntyna, V. A.; Skobeeva, V. M.; Verheles, K. A.; Malushin, M. V. (Physics and Chemistry of Solid State, 2017)
The influence of methylene blue (MB) and acridine yellow (AY) dyes on the spectra of luminescence of CdS with quantum dots (QD) dye composites is investigated. It is shown that the luminescence spectrum of the heterosystem of nanocrystals (NC) CdS – the dye depends on the absorption region of it. The spectrum of the luminescence of the quantum dots is shifted to the red region by the introduction into the colloidal solution of the MB dye and in a case of the insertion of AY the spectrum is shifted into the blue region. The obtained results are explained in a point of view of the transferring the energy from the CdS quantum dots to the dyes by the Forster mechanism.